Regional climate change in the basin of the Ile (Journal of Geography and Environmental Management, 2019)
In the works devoted to the study of climate change, explores, mainly, the fluctuations in time of the air temperature and precipitation, as on these elements the longest and most reliable series of observations. The accumulation of multi-year series of instrumental records provides the opportunity to objectively analyze the fluctuations in climate that have occurred over recent years.To clarify the trends of climate change based on recent data presented, the analysis of annual air temperature and precipitation at 13 representative meteorological stations covering the entire length of the river Ile in the Kazakhstan part. The significance of the change trend of air temperature and precipitation was tested using the statistical Mann-Kendall test. The statistical test selected for 5 meteorological stations of the 13 representative for the observation period from the opening of meteorological stations until 2016. The results of the study shows that the intensity of increase in average annual air temperature in the area of the basin of the sludge gradually increases in the direction of flow of the river, it means the smallest increase in air temperature occurred in the upper reaches, and the greatest increase in the lower reaches of the river (0,30-0,400C/10 years). In this region there is not statistically significant, bi-directional trend in annual precipitation amounts.